Условия колеблемости и неколеблемости решений одного класса полулинейных дифференциальных уравнений второго порядка - Евтухов, В.М.; Васильева, Н.С. (Український математичний журнал, 2007)
For a class of second-order semilinear differential equations, we prove theorems on oscillatory and nonoscillatory nature of all proper solutions. These theorems are analogs of the well-known Kneser theorems for linear differential equations.